Pemberdayaan Masyarakat Desa Tumpak Kecamatan Pujut Lombok Tengah Melalui Pelatihan Uji Kelayakan Instalasi Listrik - Agung Budi Muljono; Nrartha I Made; Sultan Sultan; Ginarsa I Made; Adnyani Ida Ayu Sri; Paniran Paniran; Yadnya Made Sutha; Sasongko Sudi Mariyanto Al (Jurnal Gema Ngabdi, 2023)
The increasing demand for electrical energy, especially in the household sector, requires the use of electrical equipment with electrical installations that meet the safety standard criteria according to SNI: 0225 (PUIL 2011). Electrical energy provides great benefits for human life, but it is also a threat to human life. This can happen if you do not comply with the standards for installing and using electrical installation equipment in accordance with SNI: 0225 (PUIL 2011) and Minister of Energy and Mineral Resources No. 045 of 2005, as well as behavior that is not wise and proper in using electrical equipment. As one of the villages in the KEK Mandalika area, Tumpak village has the potential to develop eco-friendly tourism, so it is necessary to prepare human resources with knowledge of electrical installations. Through community empowerment activities there has been an increase in the ability of participants in terms of theory and practice of the electrical installation feasibility test with an average value of 58.998 to 81.98 or an average increase of 38.95%.